Multidrug-Resistant Staphylococcus aureus in Diabetic Foot Infections (DFI) from Beira, Mozambique: Prevalence and Virulence Profile - Chaves CRS; Salamandane C; Maurício BDS; Machamba AAL; Salamandane A; Brito L (Infection and Drug Resistance, 2025)
Celso Raul Silambo Chaves,1 Cátia Salamandane,2,3 Beatriz da Sorte Maurício,2 Almeida Abudo Leite Machamba,2 Acácio Salamandane,2,4 Luísa Brito4 1Laboratório Clínico do Centro de Saúde de Militar de Matacuane, Avenida Alfredo Lawley No. 42, Beira, Mozambique; 2Faculdade de Ciências de Saúde, Universidade Lúrio, Campus Universitário de Marrere, Nampula, 4250, Mozambique; 3Laboratório de Qualidade e Segurança Alimentar, Centro de Estudos Interdisciplinar Lúrio, Universidade Lúrio, Campus Universitário de Marrere, Nampula, 4250, Mozambique; 4LEAF—Linking Landscape, Environment, Agriculture and Food Research Center, Associate Laboratory TERRA, Instituto Superior de Agronomia, Universidade de Lisboa, Lisboa, 1349-017, PortugalCorrespondence: Cátia Salamandane, Faculdade de Ciências de Saúde, Universidade Lúrio, Campus Universitário de Marrere, Nampula, 4250, Mozambique, Email csalamandane@unilurio.ac.mzIntroduction: Diabetic foot infection (DFI) represents a growing public health problem in Africa, caused by several microorganisms, with Staphylococcus aureus being one of the most prevalent pathogens associated with subsequent complications. This study aimed to characterize S. aureus isolated from the wounds of patients with type 2 diabetes, treated at a health center in Beira, Mozambique, in terms of antibiotic resistance and virulence genes.Methods: Samples were collected by swab, after ulcer debridement, and cultivated onto mannitol salt Columbia agar supplemented with 5% sheep blood, for 24 to 48 h, at 37°C. The antibiotic resistance was assessed by disk diffusion on Mueller–Hinton agar, and Multiplex PCR was used to screen 32 virulence and seven antibiotic resistance genes.Results: S. aureus isolates showed high phenotypic resistance to penicillin (100%), cefoxitin (53.3%), trimethoprim/sulfamethoxazole (40%) and vancomycin (22.2%), and a high percentage of multidrug resistance (68.9%). The most prevalent resistance genes were blaZ (penicillin, 100%), mecA (cefoxitin, 53.3%) and vancA (vancomycin, 28.9%). The most frequent virulence genes were TSST (toxic syndrome staphylococcal toxin, 57.8%), and the colonization factor clfB (37.8%), followed by the Panton-Valentine leukocidin (PLV) genes, lukPV (26.7%) and lukED (15.6%). The regulator factor coded by arcA (37.8%) and the adhesion factors coded by cap5 (20%) and by icaA (17.8%) were also found.Conclusion: A high presence of virulence genes encoding exotoxins and colonization and adhesion factors, associated with a high rate of multidrug resistance, was found in S. aureus isolates. This anticipates increasing difficulty in treating DFI. The greatest resistance was to commonly used antibiotics, particularly penicillin, cefoxitin and vancomycin, with resistance genes, blaZ, mecA and vancA, frequently detected. This emphasizes the urgent need for improved antimicrobial stewardship, routine molecular surveillance, and improved management strategies for DFI in resource-limited settings to mitigate disease complications and reduce the burden of antimicrobial resistance.Keywords: diabetic foot infection, DFI, Beira-Mozambique, multidrug-resistance, methicillin resistant Staphylococcus aureus, MRSA, staphylococcal exotoxin genes